Body Mass Index, Physical Activity, Cardiorespiratory Endurance and Quality of Life among Children with Physical Disabilities - Nimale Supramaniam; Asfarina Zanudin; Nor Azura Azmi (MDPI AG, 2023)
Background: Children with physical disabilities (PD) have reduced levels of physical activity (PA) compared to typically developing children, which increases their risk of becoming overweight and obese, which leads to numerous adverse health consequences. This study aimed to determine the differences between groups classified by body mass index (BMI) percentile in terms of PA levels, cardiorespiratory endurance and quality of life (QoL), and also to evaluate the relationship between BMI percentile and PA levels, cardiorespiratory endurance and QoL in children and adolescents with physical disabilities. Methods: A total of 172 children and adolescents with PD aged between 5 and 17 years from Hospital Tunku Azizah were included in this cross-sectional study. The BMI percentile was calculated to determine the weight status. PA levels were assessed with the Physical Activity Questionnaire for Older Children (PAQ-C), cardiorespiratory endurance was measured by the Six-Minute Walk Test (6MWT) and QoL was measured by the Paediatric Quality of Life Inventory version 2.0 (PedsQL 2.0). Results: According to the BMI percentile, 70.3% had a healthy BMI percentile (50th to 84th percentile), 11.6% were overweight (50th to 84th percentile), 11% were underweight (0-49th percentile) and 7.0% were obese (95th percentile and above). Most children reported a healthy weight, and the rates of being overweight and obese were higher in children who could ambulate without aids (6.4% and 3.5%, respectively) compared to those who used walking aids (5.2% and 3.5%, respectively). Significant differences were found in the PAQ-C, 6MWT and PedsQL 2.0 scores between different BMI percentile groups (p < 0.05). There were also significant correlations between the BMI percentile and the PAQ-C (r = 0.209, p < 0.001), 6MWT (r = 0.217, p < 0.001) and PedsQL 2.0 (r = 0.189, p < 0.001). Conclusion: The rate of being overweight and obese is greater among children who ambulate without aids than among those with aids. An increase in the BMI percentile can reduce the QoL in different ways. This study suggests that children with PD who can walk without aids are at a greater risk of being overweight and obese. Hence, the engagement of this population in PA is crucial for their weight management.